2016
DOI: 10.1371/journal.ppat.1005489
|View full text |Cite
|
Sign up to set email alerts
|

PKR Transduces MDA5-Dependent Signals for Type I IFN Induction

Abstract: Sensing invading pathogens early in infection is critical for establishing host defense. Two cytosolic RIG-like RNA helicases, RIG-I and MDA5, are key to type I interferon (IFN) induction in response to viral infection. Mounting evidence suggests that another viral RNA sensor, protein kinase R (PKR), may also be critical for IFN induction during infection, although its exact contribution and mechanism of action are not completely understood. Using PKR-deficient cells, we found that PKR was required for type I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 99 publications
(127 reference statements)
3
91
0
2
Order By: Relevance
“…The CARDs of RIG-I and MDA5 are responsible for transducing signals to the downstream adaptor MAVS through CARD-CARD interactions (59,60,64,65).To investigate whether CV-A16 3C pro also antagonizes RIG-I-induced MAVS activation in the RLR pathway, we performed an IFN-␤ luciferase assay in HEK293T cells. A RIG-IN expression vector, which includes the caspase recruitment domain, was employed (64,66).…”
Section: Resultsmentioning
confidence: 99%
“…The CARDs of RIG-I and MDA5 are responsible for transducing signals to the downstream adaptor MAVS through CARD-CARD interactions (59,60,64,65).To investigate whether CV-A16 3C pro also antagonizes RIG-I-induced MAVS activation in the RLR pathway, we performed an IFN-␤ luciferase assay in HEK293T cells. A RIG-IN expression vector, which includes the caspase recruitment domain, was employed (64,66).…”
Section: Resultsmentioning
confidence: 99%
“…All three RLRs are RNA helicases, and RIG-I and MDA5 additionally possess N-terminal caspase recruitment domains (CARDs) to activate the antiviral signaling chain via the CARD-containing adapter MAVS [3]. Whereas RIG-I mainly responds to short 5 0 triphosphorylated (5 0 ppp) blunt-ended double-stranded (ds) RNA with a minimal length of 10 base pairs, MDA5 is triggered by longer double-stranded dsRNA, ideally with a higher-order structure [2,[4][5][6]. For LGP2, the picture emerges that it is a negative regulator of RIG-I, but a positive regulator of MDA5 [7,8].…”
Section: Rig-i-like Receptorsmentioning
confidence: 99%
“…A recent report has shown that the dsRNA sensor PKR works downstream of MDA5 and upstream of MAVS, leading to MAVS-dependent type I IFN induction [38]. Our data suggest that DNAJB1 is involved in the MDA5-MAVS axis, but not RIG-I or TICAM-1.…”
Section: Discussionmentioning
confidence: 49%
“…Our data suggest that DNAJB1 is involved in the MDA5-MAVS axis, but not RIG-I or TICAM-1. PKR does not interact with RIG-I but is involved in MDA5-MAVS signaling [38]. Furthermore, dsRNA-mediated PKR signaling is dependent on MAVS, but not TICAM-1 [39].…”
Section: Discussionmentioning
confidence: 96%